La depressione post partum e la relazione madre-bambino - Aiello, Daniela (Il sogno della farfalla, 2019)
The onset of depression occurring in mothers after the newborn’s birth and within his/her first year of life is often a complex event difficult to diagnose. In fact, in the absence of macroscopic symptoms this disease might remain undetected. The stigma and the sense of shame experienced by women immediately after birth make the subclinical picture silent even for long period. As a consequence, the mother’s state will inevitably affect the newborn psychic development. Since last century, many authors have been studying early mother-newborn relationship making a significant impact on mother’s depression and mother-newborn relation theory. To date, a number of scientific studies describe different aspects and hypothesize that post partum depression may play a crucial role in the relationship with the newborn, affecting child development until adolescence on different levels: psychopathological, emotional, physical and behavioural. The objective of this research is to provide a different interpretation of the preverbal relationship between the mother and the newborn characterized of fantasy and images . A new idea of maternity conceived as a dialectic between two subjects, a meaningful research on the complexity of maternal experience might give women a new identity and preserve children’s health who will be the dreamers of the future.